The use of dried spent yeast as a low-cost nitrogen supplement in ethanol fermentation from sweet sorghum juice under very high gravity conditions - Sridee, Worawut; Laopaiboon, Lakkana; Jaisil, Prasit; Laopaiboon, Pattana (Electronic Journal of Biotechnology, 2011)
Dried spent yeast (DSY) was used as a low-cost nitrogen supplement for ethanol fermentation from sweet sorghum juice under very high gravity (VHG) conditions by Saccharomyces cerevisiae NP 01. The fermentation was carried out at 30ºC in a 5-litre bioreactor. The results showed that DSY promoted ethanol production efficiencies. The ethanol concentration (P), productivity (Qp) and yield (Yp/s) of the sterile juice (total sugar of 280 g l-1) supplemented with 8 g l-1 of DSY were not different from those supplemented with yeast extract and/or peptone at the same amount. The initial yeast cell concentration of 5 x 107 cells ml-1 was found to be optimal for scale-up ethanol production. In addition, an increase in sugar concentration in inoculum preparation medium (from 10 to 100 g l-1) improved the ability of the inoculum to produce ethanol under the VHG conditions. When S. cerevisiae NP 01 grown in the juice containing 100 g l-1 of total sugar was used as the inoculum for ethanol fermentation, the P, Qp and Yp/s obtained were 108.98 ± 1.16 g l-1, 2.27 ± 0.06 g l-1 h-1 and 0.47 ± 0.01 g g-1, respectively. Similar results were also observed when the ethanol fermentation was scaled up to a 50-litre bioreactor under the same conditions. The cost of the sweet sorghum for ethanol production was US 0.63 per litre of ethanol. These results clearly indicate the high potential of using sweet sorghum juice supplemented with DSY under VHG fermentation for ethanol production in industrial applications.